SHE Control for PV System Connected to the Grid - Maha Khanfara; Rachid EL Bachtiri; Oumaima Khanfara; Mohammed Boussetta; Karima EL Hammoumi; Imane Idrissi (Universitas Ahmad Dahlan, 2018)
In this article, we have proposed a new control of a PV system connected to the grid. The goal is to reduce current and voltage harmonicsfor increasing the quality of delivered energy. First, we have modeled a PV panel. Then we have dimensioned the BOOST converter by finding L and C values. Next, we have used Perturb and Observe (P&O) Maximum Power Point Control (MPPT) to improve energy efficiency. Finally, We have developed a control of single-phase H-bridge inverter in order to eliminate the 3rd,5th,7th and 9th harmonics order, and added an LCLTo connect the PV inverter to the grid, an LCL betweenthe inverter and the grid. Theperformance of the proposed system was tested by computing spectrum and THD usingMatlab/Simulink software. The proposed architecture provides better Total Harmonic Distortion (THD) which satisfy the EN50160 requirement the THD must be less than 4.66%. We found that THD was decreased from 61.93% to 0.04%.